(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Recently, breast cancer has been considered as an increasing problem specially in Iraq . This study was designed to investigate maternal risk factors of breast cancer in Al-Najaf Province . A Convenience sample of (40) patients was taken in this study during the period from Dec. .2019 to Apr. 2020 . The result of the present study shows that the majority of the women were between the age (30-40) years show the breast cancer increase in this age group. The results of the current study also showed that the vast majority at the women were married. The current study also showed that about (27.5%) and (22%) at the studied women are suffering from hypertension and diabetes mellitus respectively. The present study reveal that about (32.5)of the women did not practice breast feeding ,(42.5) of them less than 2 years breast feeding. The present study revealed that about 60%of the women didn’t exposed to passive smoking and 40% of the women exposed to passive smoking , other study explain the second hand smoke have been suggested to increase the risk of breast cancer. The present study indicated that approximately all investigated women (39of 40)have no medical history of ovarian polycystic disease . It was concluded that the most contributing risk factors in the occurrence Education, BMI , contraceptive use ,passive smoking and age. It is recommended to establish an education program to enhance the awareness of women about the risk factors that have been recorded in this study .